(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This research aims to highlight the impact of strategic leadership, with its five dimensions—strategic vision, core competencies, human capital, organizational culture, and ethical practices—on stimulating and developing organizational energy in its three dimensions: cognitive energy, emotional energy, and behavioral energy, at the Technical Institute/Baquba. To achieve the research objectives, the descriptive-analytical method was used, and a questionnaire was developed as the primary data collection tool. The questionnaire was distributed to a purposive sample of 50 respondents, including administrative leaders, faculty members, and staff. The statistical results indicated a significant correlation and a strong positive effect between strategic leadership and levels of organizational energy, supporting the research’s main hypotheses. One of the most important conclusions is that adopting a strategic leadership approach can contribute to developing and increasing the effectiveness of organizational energy, as confirmed by the recorded correlation and effect relationships. The research recommends incorporating concepts for enhancing organizational energy into the institute’s strategic planning to improve the institution’s ability to respond to the challenges of modern education.